Strategies for developing competitive advantage to increase customer satisfaction in the logistics business in Indonesia - Mhd Ramadhan; Efendi Efendi; Robert Tua Siregar; Randika Saragih; Agus Siswanto (Lembaga Riset Mutiara Akbar (LARISMA), 2026)
This study aims to analyze competitive advantage development strategies to improve customer satisfaction in the logistics business in Indonesia. Increasingly fierce competition demands logistics companies to be able to create superior value through service quality and customer value. This study uses a quantitative approach with a survey method of logistics service users, with data collection through an online questionnaire. The variables studied include service quality, customer value, competitive advantage, and customer satisfaction. Data analysis was conducted using the Structural Equation Modeling (SEM) method to test the relationship between variables. The results show that service quality and customer value have a positive and significant effect on competitive advantage. In addition, service quality, customer value, and competitive advantage also have a positive and significant effect on customer satisfaction. These findings indicate that improving service quality and creating customer value can effectively enhance a company's competitive advantage. A strong competitive advantage will impact on increasing customer satisfaction with the services received. Therefore, logistics companies need to continue to develop strategies that focus on improving service quality and customer value to maintain competitiveness and increase customer satisfaction sustainably.